Introversion Personality and Students’ Reading Comprehension - Samsi Hasan; Nurmi Yulianti (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2018)
Introversion is characterized by social isolation and introspective nature. In the process of learning English as a foreign language, it is important to understand learner’s personalities. This is because each individual language learner has different tendencies and can influence the effectiveness and success of learning the four main skills of the language. The aim of this study is to investigate the relationship between introversion personality and students’ reading comprehension. 95 eleventh-grade upper secondary students were randomly selected for this study. The researchers used a questionnaire to measure students’ introversion personality, and a test to measure their reading comprehension. Serial Correlation Coefficient formula was employed as the main method to analyze the data. Based on the analysis, it was found that both the students’ introversion personality and reading comprehension was categorized as average. This indicated that introversion personality and students’ reading comprehension were significantly correlated. The correlation between the two variables were strong. Therefore, it can be concluded that introversion personality played an important role in affecting students’ reading comprehension. Thus, the more introverted the students, the better their reading comprehension.